A multi-centre international study of salivary hormone oestradiol and progesterone measurements in ART monitoring. Issue 2 (February 2021) - Sakkas, Denny; Howles, Colin M.; Atkinson, Leslie; Borini, Andrea; Bosch, Ernesto A.; Bryce, Crystal; Cattoli, Monica; Copperman, Alan B.; de Bantel, Astrid Finet; French, Brian; Gerris, Jan; Granger, Steve W.; et al.
Abstract: Research question: Ovarian stimulation during IVF cycles involves close monitoring of oestradiol, progesterone and ultrasound measurements of follicle growth. In contrast to blood draws, sampling saliva is less invasive. Here, a blind validation is presented of a novel saliva-based oestradiol and progesterone assay carried out in samples collected in independent IVF clinics. Design: Concurrent serum and saliva samples were collected from 324 patients at six large independent IVF laboratories. Saliva samples were frozen and run blinded. A further 18 patients had samples collected more frequently around the time of HCG trigger. Saliva samples were analysed using an immunoassay developed with Salimetrics LLC. Results: In total, 652 pairs of saliva and serum oestradiol were evaluated, with correlation coefficients ranging from 0.68 to 0.91. In the European clinics, a further 237 of saliva and serum progesterone samples were evaluated; however, the correlations were generally poorer, ranging from –0.02 to 0.22. In the patients collected more frequently, five out of 18 patients (27.8%) showed an immediate decrease in oestradiol after trigger. When progesterone samples were assessed after trigger, eight out of 18 (44.4%) showed a continued rise. Conclusions: Salivary oestradiol hormone testing correlates well to serum-based assessment, whereas progesterone values, around the time of trigger, are not consistent from patient to patient.